Вклад архитекторов польского происхождения в становление и раз- витие курортов Кавказских Минеральных Вод (XIX – начало XX века) - Акопян, Виктор (Acta Polono-Ruthenica, 2021)
Caucasian Mineral Waters (Kavminvody, KMV) is a group of North Caucasian balneological resorts of federal significance in the Stavropol Territory. The CMS region includes the resort cities of Pyatigorsk, Kislovodsk, Zheleznovodsk, and Yessentuki. By the decree of Emperor Alexander I of 1803, their official existence as a resort area began. Representatives of the Polish people began to arrive there from the very beginning. They made up a significant proportion of the officers, managers, and intellectuals: scientists, doctors, engineers, architects, teachers, and writers. This article opens a portrait gallery dedicated to the activities of outstanding architects and civil engineers of Polish origin in Kavminvody, thanks to whose contribution the KMV resorts have acquired a worthy appearance and world fame. The results of their work today continue to serve as a fundamental basis and a model for further development of the resorts